Counselling Services: The Albatross of Students with Disabilities in the Pan African University in Ghana - Gyasi, Ficus; Hayford, Samuel K. (IJRDO- Journal of Educational Research, 2017)
Universities set up counselling centres to provide services for students, including those withdisabilities, to mitigate the challenges they encounter while schooling, in order to enhance theirparticipation in academic work and social life. However, investigation conducted by theresearchers revealed that the Counselling Centre in Pan African University in Ghana hasbecome an albatross to students with disabilities. This paper describes the factors that haveturned the Counselling Centre into an albatross for students with disabilities in the Pan AfricanUniversity in Ghana. The purpose of the study was to ascertain whether or not counsellingservices in the Pan African University were accessible to students with disabilities. A sample of18 students with disabilities (six visually impaired, six hearing impaired and six physicallydisabled, respectively) was purposefully selected using maximal variation approach. Semistructuredinterviews were used to collect data for the study. The researchers adopted thematicanalysis to analyze the data. The results showed that students with disabilities were unable toaccess the much needed counselling service provided by the university due to barriers related tothe location of the counselling centre and communication. These barriers adversely impacted onthe students’ moral and academic achievements. The students suggested that the Universityshould decentralize the counselling services to make the services more accessible. Theresearchers recommended that the University should provide in-service training focusing onissues in disabilities for the professional counsellors in the University.